2013
DOI: 10.1073/pnas.1220826110
|View full text |Cite|
|
Sign up to set email alerts
|

Cognitive relevance of the community structure of the human brain functional coactivation network

Abstract: There is growing interest in the complex topology of human brain functional networks, often measured using resting-state functional MRI (fMRI). Here, we used a meta-analysis of the large primary literature that used fMRI or PET to measure task-related activation (>1,600 studies; 1985–2010). We estimated the similarity (Jaccard index) of the activation patterns across experimental tasks between each pair of 638 brain regions. This continuous coactivation matrix was used to build a weighted graph to character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
335
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 438 publications
(376 citation statements)
references
References 50 publications
26
335
1
Order By: Relevance
“…It has been shown that higher-IQ individuals tend to have more-efficient structural and functional networks (24,25), that more-difficult cognitive tasks demand more-integrated or efficient functional network topology (26,27), and that a pharmacological challenge (acute nicotine replacement in abstinent cigarette smokers) that enhanced attention also increased efficiency and connection distance of fMRI networks (28). These observations are consistent with earlier theoretical claims that higher-order conscious processing depends on access to a "global workspace" rather than a segregated, modular architecture (29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that higher-IQ individuals tend to have more-efficient structural and functional networks (24,25), that more-difficult cognitive tasks demand more-integrated or efficient functional network topology (26,27), and that a pharmacological challenge (acute nicotine replacement in abstinent cigarette smokers) that enhanced attention also increased efficiency and connection distance of fMRI networks (28). These observations are consistent with earlier theoretical claims that higher-order conscious processing depends on access to a "global workspace" rather than a segregated, modular architecture (29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the brain's network architecture during task performance is shaped primarily by the network architecture present during resting state (i.e., spontaneous neural activity), as spontaneous neural activity is likely a prior or constraint on task activity (31,32). This has been demonstrated in humans using fMRI (33)(34)(35)(36)(37), in monkeys using multielectrode recordings (38), and in zebrafish using two-photon Ca 2+ imaging (39). Thus, predictions regarding the brain's network structure-and potentially nodes' activity magnitudes-during tasks can be made based on the brain's network structure during spontaneous neural activity.…”
Section: Significancementioning
confidence: 99%
“…However, their approach focused on distinguishing cognitive states across fMRI‐sessions [see also Shirer et al, 2012], rather than detecting state‐changes within a single session. Crossley et al [Crossley et al, 2013] used graph analysis to examine a large dataset of task‐related PET and fMRI experiments, which revealed the recurrent coactivation of distinct areas across experiments/tasks. These results confirmed the possibility of using network configurations to track cognitive function in a data‐driven manner, but again without providing us any time‐resolved information for event‐categorization within a fMRI time‐series/experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Because the identification of network configurations via coactivation does not rely directly on the BOLD signal, the areas belonging to the same network can have markedly different signal [cf., also CAPs, above; and “competitive interactions,” in Crossley et al, 2013]. Here, the characteristics of the BOLD signal within each area were examined further with the second clustering step (BOLD‐clustering).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation